RANCANG BANGUN APLIKASI MEDIA JASA DESAIN LOGO DENGAN METODE WATERFALL BERBASIS WEBSITE - Raden Bagus Bambang Sumantri; Willy Setiawan; Deny Nugroho Triwibowo (Universitas Methodist Indonesia, 2022)
The rapid development of internet technology has a huge influence on people's daily lives. Internet technology provides convenience for people to convey information quickly, one of them through the media website. Website is one of the right choices to convey information because it is more accessible from various places and regions just by using the internet. Design website as a promotional media logo design services is aimed to be a solution to the lack of promotional media logo design services on CV Jenester. The results of the website design will be used as a promotional media logo design services to expand the reach of promotion to the public through the internet. The method used in the design and construction of the website is a waterfall method included in one of the SDLC (Software Development Life Cycle) methods that have several stages ranging from analysis, design, coding, testing, and support. The result of website design is the implementation directly to the internet through web hosting. Website design is expected to be a solution to the lack of media promotion of logo design services on CV. Jenester.